THU0471 Myeloid Deletion of SIRT1 Suppresses Collagen-Induced Arthritis in Mice by Modulating Dendritic Cell Function. (10th June 2014) - Kim, H.-O.; Suh, Y.S.; Lee, I.-I.; Lim, H.S.; Cheon, Y.-H.; Yoo, W.-H.; Lee, W.-S.; Park, B.-H.
Abstract : Objectives: The type III histone deacetylase SIRT1 is a critical molecule in the modulation of immune and inflammatory response through the deacetylation of various histones and non-histone proteins. However, there are limited and controversial data regarding the roles of SIRT1 in rheumatoid arthritis (RA) and its role in dendritic cells (DCs) remains unknown. Thus, this study sought to assess the role of SIRT1 in collagen-induced arthritis (CIA) using a myeloid cell-specific SIRT1 knockout (mSIRT1 KO) mouse. Methods: mSIRT1 KO mice were generated using the loxP/Cre recombinase system. CIA was induced in mSIRT1 KO mice and age-matched littermate loxP control mice. Arthritis severity was assessed by clinical, radiological, and pathological scoring. The levels of various cytokines in the joints, serum, lymph nodes were determined by quantitative polymerase chain reaction and ELISA. T cells and DCs were quantified using flow-cytometry and in vitro T cell cytokines and DCs markers were also measured. Results: The mSIRT1 KO mice showed significantly lower arthritis severity and joint destruction compared with control mice. The expression of inflammatory cytokines, MMPs, and ROR-γT was also reduced in mSIRT1 KO mice. These effects were paralleled by reduction of Th1, Th17, CD69-positive T cells, CD80, and CD86 positive DCs in mSIRT1 KO mice. In addition, in vitro studies showed that interferon-γ and IL-17 production by T cells and the maturation of DCs were significantly decreased in mSIRT1 KO mice. Conclusions: Unlike passive K/BxN serum transfer arthritis, myeloid cell-specific deletion of SIRT1 was associated with lower arthritis severity in CIA by modulating DCs maturation and Th1 and Th17 responses. The data suggest that SIRT1 plays a complex role in RA and careful investigation of cell-specific effects is necessary to delineate possible therapeutic uses of agents targeting SIRT1. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4188